2014
DOI: 10.1097/mib.0000000000000018
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Effects of Smoking in Ulcerative Colitis and Crohnʼs Disease May Be Explained by Differential Effects on Dendritic Cells

Abstract: CSE modulates DC phenotype and function in patients with UC leading to increased prevalence of Foxp3+ CD4 T cells, whereas in patients with CD it skews toward Th1 subsets. Differential DC responses to CSE between CD and UC may contribute to the differential effects associated with cigarette smoking status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…chemical- vs. pathogen-induced colitis) to trigger intestinal damage, as smoking by itself does not result in spontaneous enterocolitis in most animal models (70). Nonetheless, in vitro application of cigarette extract on patient-derived dendritic cells showed that it increased the prevalence of Foxp3+ CD4 T cells in UC whereas it skewed toward Th1 subset in CD (71), suggesting a possible differential effect in immune cells in CD vs. UC. One possible scenario is that to trigger/aggravate IBD requires combinations of specific sets of genes and smoking exposure, thereby explaining the seemingly different effects in patients from different ethnic groups.…”
Section: Identifying Environmental Factorsmentioning
confidence: 99%
“…chemical- vs. pathogen-induced colitis) to trigger intestinal damage, as smoking by itself does not result in spontaneous enterocolitis in most animal models (70). Nonetheless, in vitro application of cigarette extract on patient-derived dendritic cells showed that it increased the prevalence of Foxp3+ CD4 T cells in UC whereas it skewed toward Th1 subset in CD (71), suggesting a possible differential effect in immune cells in CD vs. UC. One possible scenario is that to trigger/aggravate IBD requires combinations of specific sets of genes and smoking exposure, thereby explaining the seemingly different effects in patients from different ethnic groups.…”
Section: Identifying Environmental Factorsmentioning
confidence: 99%
“…To date, the exact mechanisms which underlie the differential effects of CS on CD and UC remain a matter of debate. For example, it has been suggested that differential DC responses to CS between CD and UC may play a role [139]. Another study suggests that CS induces barrier dysfunction in the ileum, but not in the colon [140].…”
Section: Impact Of Cs On Trp Channels In the Gut?mentioning
confidence: 99%
“…Similarly, the same investigators demonstrated that smokers with CD had significantly lower IL-10 (anti-inflammatory)/IL-12 (pro-inflammatory) ratios than non-smokers or smokers with UC. As suggested in some reports, the differential signalling of dendritic cells from CD (Th1-like) and UC patients exposed to cigarette smoke extract (CSE) in vitro could play a role in the opposing responses of cigarette smoke exposure, that is, a Th1-like response in CD, with increased Foxp3-positive CD4 T cells [121].…”
Section: Immune Regulationmentioning
confidence: 99%